The evolutionary synthesis : perspectives on the unification of biology - Mayr, Ernst; Provine, William B (Harvard University Press, 1998)
Biology was forged into a single, coherent science only within living memory. In this volume the thinkers responsible for the \"modern synthesis\" of evolutionary biology and genetics come together to analyze that remarkable event. In a new Preface, Ernst Mayr calls attention to the fact that scientists in different biological disciplines varied considerably in their degree of acceptance of Darwin\'s theories. Mayr shows us that these differences were played out in four separate periods: 1859 to 1899, 1900 to 1915, 1916 to 1936, and 1937 to 1947. He thus enables us to understand fully why the synthesis was necessary and why Darwin\'s original theory—that evolutionary change is due to the combination of variation and selection—is as solid at the end of the twentieth century as it was in 1859.
Keywords: vývojová biologie; biologie; Developmental Biology